Sono-anatomy of the middle cervical sympathetic ganglion verified with pathology - Yu-Tao Lei; Yun-Xia Hao; Zhen Yang; Zhuo-Hua Lin; Wen Qin; Jun-Hao Yan; Yang Sun; Li-Gang Cui; Ying Fu (Heliyon, 2024)
Objectives: Cervical discomfort and other symptoms may be attributable to the middle cervical sympathetic ganglion. The aim of this study was to explore the sonographic features of this ganglion in anatomical specimens and cadavers and evaluate the feasibility of its visualization using high-resolution ultrasonography. Methods: We examined three cervical sympathetic-ganglion specimens and two fresh cadavers using high-resolution ultrasound to explore the sonographic features of this ganglion. Basic imaging characteristics examined included the shape, echo intensity, and location of the ganglion. Core-needle biopsy was performed to examine the suspected middle cervical sympathetic ganglion in the two fresh cadavers and verify the accuracy of the sonographic identification via pathological examination. Results: The middle cervical sympathetic ganglion appeared on high-resolution ultrasonography as an oval-shaped hypoechoic structure, with at least one continuous hypoechoic line connected to each ending in the anatomical specimens and fresh cadavers, and it was distinctly different from the adjacent lymph nodes. Discussion: Based on an adequate understanding of both its location and sonographic features, the direct visualization of the middle cervical sympathetic ganglion using high-resolution ultrasonography is feasible.